Universally Primed PCR (UP-PCR) and its applications for taxonomy in Trichoderma - Mette Lübeck (浙江大学学报. 农业与生命科学版)
Universally Primed PCR (UP-PCR) is a PCR fingerprinting method that has demonstrated its applicability in different aspects of mycology. These applications constitute analysis of genome structures, identification of species, analysis of population and species diversity, revealing of genetic relatedness at infra-and inter-species level, and identification of UP-PCR markers at different taxonomic levels (strain, group and/or species). A further development of the UP-PCR technique is an UP-PCR product cross hybridisation assay that facilitates investigation of sequence similarity (homology) of UP-PCR products and grouping of strains into UP-PCR hybridisation groups. This separates the strains into entities with high genetic similarity (DNA homology). UP-PCR has been used as an aid in taxonomy and species delineation, and to monitor biocontrol strains following their release into the environment by fingerprint characterisation of pure cultures and through direct detection in soil by amplification of UP-PCR-derived SCAR markers. The technique has been applied to Trichoderma strains in particularly with the aims of strain recognition and classification.